Analysis Of Criminal Liability As Doer Of Preening Criminal (Case Study In The Blora State Court) - Haris Wahyu Sunarno; Akhmad Khisni (Jurnal Daulat Hukum, 2020)
Criminal beatings lately occur a lot because of actions from one person to another outside the normal limits. Crimes that often occur are beatings regulated in the criminal law book, namely Article 170 of the Criminal Code. The formulation of the problem in this study is how is the form of criminal responsibility towards the perpetrators of the beating crime committed by more than one perpetrator, and what are the obstacles in the criminal justice process against the perpetrators of the beatings and their solutions. The method used in the form of sociological juridical research specifications descriptive analysis. Data consists of primary data and secondary data taken by the method of document collection, interviews, and literature study. Based on the research it was concluded (1) The form of a system of criminal justice process in the flow of the trial in the decision Number 94 / Pid.B / 2019 / PN Bla as a form of criminal responsibility towards the perpetrators of beating crimes that are processed in the criminal justice process, (2) Obstacles deep inhibition in the criminal justice process against the perpetrators of the beating crime including the investigation process in presenting witnesses, the prosecution process that takes time, and article 170 of the Criminal Code which still has ambiguous in theoretical.Keywords: Criminal Liability, Beating Criminal Acts